PUSAT KOMUNITAS SEPEDA DI KOTA PONTIANAK - Elicia Javiera; Uray Fery Andi; Yudi Purnomo (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
Bicycle is the sustainable land transport. The background of this design is the cycling trend in Pontianak City has existed since 2000. In 2005 the Bike to Work community was formed and until now more than 20 bicycle communities have been formed in Pontianak City. Members of the cycling community need a place to gather and share their interest in cycling, and people need a safe place to play and practice cycling. This design is in line with the commitment of the Pontianak City Government to realize Pontianak City as a bicycle-friendly city. The main purpose is to provide an interactive, flexible, and combine meeting point with the shape of bicycle wheels as part of the design. The design used the Whitaker design method, which consists of the introduction stage, definition stage, preparation stage, analysis stage, synthesis stage, evaluation stage, and re-evaluation stage. The main concept is to create eight bicycle community clusters that are integrated with commercial, recreational, and educational areas to meet the needs and lifestyles of cyclists. This design produces a plaza area with an arrangement of eight bicycle clusters that are centralized and integrated with a commercial area, waterfront, food court, and freestyle area with cluster organization.